High School Students’ Argumentation Skills: A Study of Sundanese High School Students’ Opinion-forming Skills about Human Cloning Issues - Bambang Ekanara; Ilma Riksa Isfiani (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
Science education has progressed very rapidly both in terms of content and skills as learning experiences. This progress must be responded to by every student and their background, including Sundanese people. Cloning is one aspect of science education content that goes along its controversy, so that argumentation skills are very suitable for every student. It is hoped that they will form opinions based on their point of view on the issue. Sundanese people are known to be simple and to keep their ancestral knowledge from generation to generation. Therefore, it will be very interesting to research how they form opinions on the issue of cloning. This study aimed to investigate the argumentation skills of the eleventh-grade students of a Sundanese High School about Human cloning based on gender and cultural habits. This qualitative research probed argumentation skill quality by claim forming and evidence supplying. Forty-four students of the eleventh-grade were given a research instrument with a snowball sampling technique. Students’ worksheet of cloning was used to trawl data of written argumentation skills. Semi-structured interviews encompassed oral argumentation skills data. The family’s gender awareness data were obtained through questionnaires and interviews. Furthermore, this research utilized a data triangulation tool by using field notes. Four-scale rubrics were used to determine students’ argumentation skills with inductive analysis as a tool to examine the data. The results show that most of the research subjects (Sundanese students) can create simple argument can create mentation skills better than written argumentation skills with relatively no significant differences based on gender differences. According to this research finding, several factors influencing Sundanese students' argumentation skills, such as freedom of opinion-forming in family life, students' role in the family, articulating ideas, and cultural influences, are suggestions.